Proteoglycan synthesis in the intervertebral disk nucleus: The role of extracellular osmolality - Ishihara, H; Warensjo, K; Roberts, S; Urban, J (1997)
Proteoglycans, through their polyelectrolyte properties, regulate the ionic composition and hence the osmotic pressure of the extracellular matrix. We measured the change in [35S]sulfate incorporation, a marker of proteoglycan synthesis, in explants of bovine nucleus pulposus. During incubation, nucleus slices swelled 200% and proteoglycans leached from the matrix, so that extracellular osmolality fell from 420-450 to ~300 mosmol/kgH2O. When in vivo extracellular osmolality was maintained either by adding 80 mM NaCl or 150 mM sucrose to the swollen tissue or by preventing swelling, synthesis rates were 260-280% greater than in swollen tissue. Synthesis rates also increased 200% in cells isolated from the nucleus pulposus by enzyme digestion when medium osmolality was raised from 280 to 430 mosmol/kgH2O by sucrose addition. The cells, either in the tissue or isolated from it, swelled by more than 20% as osmolality fell from 430 to 280 mosmol/kgH20 and showed little regulatory volume decrease over 150 min. Synthesis rates thus appear to be regulated by extracellular osmolality rather than by the macromolecular composition of the matrix and correlated well with measured changes in cell volume.